2013
DOI: 10.1007/s12262-013-1015-0
|View full text |Cite
|
Sign up to set email alerts
|

Rural Surgery in Niger: A Multicentric Study in 21 District Hospitals

Abstract: The purpose of the study was to evaluate the qualitative aspect and global impact of surgery in a district hospital (DH) since the launching of the surgery at the district level. Surgical care was provided by general practitioners (GP) who received 12-month training in surgery, certified by a "Capacity of District Surgery" (CDS) diploma. It was a prospective study during 4 years from 2007 to 2010. Of the 34 DHs, only 21 were functional and included in this study. Most of the DHs had two or more CDS (n =15). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In rural or low resource settings, training may be focused on the basic ability to perform any inguinal repair for patients with significant symptoms without causing mortality or serious morbidity (see also Chapter 28). 1 …”
Section: Training and The Learning Curvementioning
confidence: 99%
“…In rural or low resource settings, training may be focused on the basic ability to perform any inguinal repair for patients with significant symptoms without causing mortality or serious morbidity (see also Chapter 28). 1 …”
Section: Training and The Learning Curvementioning
confidence: 99%
“…Overall, of the 1101 post‐training inguinal hernia repairs, only 89 were repaired with mesh due to a shortage of mesh supply. Included studies mostly reported anecdotal qualitative capacity‐building effects (Table 3) such as: the feasibility of prospective research in limited‐resource settings [9], improved access to surgical care [12, 13], change in practice pattern of local physicians after training for mesh repair [10, 14], and a higher likelihood that trained clinical officers stay in the country and in rural areas [15].…”
Section: Resultsmentioning
confidence: 99%
“…Between 2013 and 2015, surgical training of COs increased the volume of procedures performed by 74%. Sani et al [13] reported on the Capacity of District Surgery initiative which included a 12‐month surgical training of general practitioners and senior nurses in Niger, Africa. Trainees were dispatched to 21 District Hospitals, and outcomes were followed between 2007 and 2010.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations